2021
DOI: 10.3390/su13137457
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on the Participation Aspects of Environmental and Nature-Based Citizen Science Initiatives

Abstract: It is commonly argued that, despite the tremendous resonance Citizen Science (CS) has shown in recent years, there is still lack of understanding of important aspects defining citizens’ participation and engagement in CS initiatives. While CS initiatives could provide a vehicle to foster forms of participation contributing to the democratization of science, there is still limited attention paid to the “Citizen” component of the Citizen Science term. For the purpose of this work, we systematically reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 120 publications
1
38
0
2
Order By: Relevance
“…More specifically, previous studies found a positive association between first-hand experiences with nature and pro-environmentalism [66][67][68], while, in contrast, dissociation from nature was found to be related to hindering support for environmental causes [69,70]. In addition, an increasing corpus of studies has provided empirical substantiation for the claim that participation in environmental and nature-based Citizen Science (CS) projects may contribute to the transformation of citizens into environmentally responsible and active citizens [26,29,71]. In its essence, participation in environmentalrelated activities implies that people contribute to the environmental management process, and, in turn, this also affects and shapes their own lives.…”
Section: Effect Of Past/present Ec Actionsmentioning
confidence: 98%
See 1 more Smart Citation
“…More specifically, previous studies found a positive association between first-hand experiences with nature and pro-environmentalism [66][67][68], while, in contrast, dissociation from nature was found to be related to hindering support for environmental causes [69,70]. In addition, an increasing corpus of studies has provided empirical substantiation for the claim that participation in environmental and nature-based Citizen Science (CS) projects may contribute to the transformation of citizens into environmentally responsible and active citizens [26,29,71]. In its essence, participation in environmentalrelated activities implies that people contribute to the environmental management process, and, in turn, this also affects and shapes their own lives.…”
Section: Effect Of Past/present Ec Actionsmentioning
confidence: 98%
“…During the last two years, researchers have collaborated at the European and international level as part of the European Network for Environmental Citizenship (ENEC) [22], trying to produce a coherent definition for "Education for Environmental Citizenship". The ENEC conceptualization has been widely used in the literature since 2018, due to its holisticness, inclusiveness and comprehensiveness [8,[25][26][27][28][29], and it is also adopted in this study. More specifically, according to ENEC: "Education for Environmental Citizenship is defined as the type of education that cultivates a coherent and adequate body of knowledge as well as the necessary skills, values, attitudes and competences that an Environmental Citizen should be equipped with in order to be able to act and participate in society as an agent of change in the private and public sphere on a local, national and global scale, through individual and collective actions in the direction of solving contemporary environmental problems, preventing the creation of new environmental problems, in achieving sustainability as well as developing a healthy relationship with nature.…”
Section: Theoretical Background 21 Defining the Education Of Environmental Citizenshipmentioning
confidence: 99%
“…All three options might present barriers for senior age groups, e.g. a (possibly) strenuous field trip, a time-consuming workshop or the handling of an unknown technology (Vasiliades et al, 2021), especially when specific information on the future design of the programme is lacking. The possible enthusiasm about the wildlife park visit that prevailed when filling out the questionnaire, as well as the leisure time capacity of the younger respondents might also have led to a positive attitude towards CS activities.…”
Section: Willingness To Participate In Citizen Sciencementioning
confidence: 99%
“…To ensure transparency and clarity when reporting systematic reviews, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) methodology was adopted for this literature study [22][23][24] (Supplementary Materials). The data for this systematic review was collected from peer-reviewed papers in several databases with a high level of academic integrity, including Google Scholar, Science Direct, Research Gate, World Cat, and Web of Science [25][26][27].…”
Section: Literature Search Strategymentioning
confidence: 99%